2015
DOI: 10.1002/cncr.29523
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in breast cancer survival in a large urban integrated health system

Abstract: BACKGROUND: African American (AA) women are known to have poorer breast cancer survival than whites, and the differences may be related to underlying disparities in their clinical presentation or access to care. This study evaluated the relationship between demographic, treatment, and socioeconomic factors and breast cancer survival among women in southeast Michigan. METHODS: The population included 2387 women (34% AA) with American Joint Committee on Cancer stage I to III breast cancer who were treated at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
(132 reference statements)
2
22
0
Order By: Relevance
“…Socioeconomic status has been shown to influence breast cancer survival outcomes when measured at both individual and area levels, with results consistently showing worse outcomes for patients with lower individual and/or area-level SES [7, 19, 23]. Fewer studies have examined other area-level factors such as access to healthcare resources [4, 24, 25], while most studies have focused on examining insurance status. However, area-level availability of healthcare resources likely plays a key role in breast cancer survival outcome through the receipt of timely and high-quality treatment, which in turn influences survival.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status has been shown to influence breast cancer survival outcomes when measured at both individual and area levels, with results consistently showing worse outcomes for patients with lower individual and/or area-level SES [7, 19, 23]. Fewer studies have examined other area-level factors such as access to healthcare resources [4, 24, 25], while most studies have focused on examining insurance status. However, area-level availability of healthcare resources likely plays a key role in breast cancer survival outcome through the receipt of timely and high-quality treatment, which in turn influences survival.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, EOL expenditures are unlike many other health outcomes that have been evaluated for the effects of race and ethnicity. Prior studies have demonstrated that other mechanisms, such as socioeconomic status, health literacy, clinical factors, hospital‐ or neighborhood‐level effects, or insurance status, can explain what often appears to be a race effect on health outcomes . Although the current study included these factors, all of which somewhat attenuated the measured association between EOL Medicare expenditures and racial and ethnic groups, they failed to explain the total difference.…”
Section: Discussionmentioning
confidence: 77%
“…Prior studies have demonstrated that other mechanisms, such as socioeconomic status, health literacy, clinical factors, hospital-or neighborhood-level effects, or insurance status, can explain what often appears to be a race effect on health outcomes. 3,4,9,11,[42][43][44][45] Although the current study included these factors, all of which somewhat attenuated the measured association between EOL Medicare expenditures and racial and ethnic groups, they failed to explain the total difference. This highlights how complexities surrounding care and decision-making at the EOL can be difficult to capture.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations